One size doesn’t fit all: teaching graphic design through a Moodle based ePortfolio - Sinfield, D (Moodlemoot (Australia), 2013)
What is becoming more and more alarming is the reduced amount of contact time we have with the students. We are seeing increased classroom numbers, and having to deliver the same content. With ever increasing budgetary restraints the learning environment for the graphic design student is being pressurised to sit in the same mound as other education programmes that operate on a more financial economical basis. The purpose of this project was to engage in out-of-class communications that would enhance the learning and teaching. This was seen as engaging with an on-line Moodle based ePortfolio area that was specifically tailored for the students so they could communicate with each other and the tutor of the class. There was also the need for the students to up-load their designs, to obtain critique from their peers and tutors whilst away from class. This would have several benefits as feedback could be given outside of class making the precious time in class much more productive. In doing so it also creates a healthy collaborative design community.